Side Effects of mRNA-Based and Viral Vector-Based COVID-19 Vaccines among German Healthcare Workers - Klugar, Miloslav; Riad, Abanoub; Mekhemar, Mohamed; Conrad, Jonas; Buchbender, Mayte; Howaldt, Hans-Peter; Attia, Sameh (Biology, 2021)
Simple Summary The main way to overcome the COVID-19 pandemic is mass vaccination of the public. However, the public's vaccine hesitancy toward the available vaccines is a big challenge in the fighting against the coronavirus spreading. We aimed in this study to report for the first time the short-term side effects following mRNA-based (Pfizer-BioNTech and Moderna) and viral vector-based (AstraZeneca) COVID-19 vaccines among German healthcare workers. A survey-based study was conducted through an online validated questionnaire. Overall, 88.1% of the German healthcare workers included in this study reported at least one side effect following the COVID-19 vaccination. The mRNA-based vaccines were associated with a higher prevalence of local side effects (e.g., injection site pain), while the viral vector-based vaccine was associated with a higher prevalence of systemic side effects (e.g., headache/fatigue). The vast majority (84.9%) of side effects resolved within 1-3 days after vaccination, which are promising results from a safety point of view for both types of vaccines. This study is one of the few studies that aims to enhance our emerging knowledge about the risk factors of COVID-19 vaccines side effects by inquiring and analyzing the self-reported side effects across various demographic and medical parameters. Background: the increasing number of COVID-19 vaccines available to the public may trigger hesitancy or selectivity towards vaccination. This study aimed to evaluate the post-vaccination side effects of the different vaccines approved in Germany; Methods: a cross-sectional survey-based study was carried out using an online questionnaire validated and tested for a priori reliability. The questionnaire inquired about demographic data, medical and COVID-19-related anamneses, and local, systemic, oral, and skin-related side effects following COVID-19 vaccination; Results: out of the 599 participating healthcare workers, 72.3% were females, and 79.1% received mRNA-based vaccines, while 20.9% received a viral vector-based vaccine. 88.1% of the participants reported at least one side effect. Injection site pain (75.6%) was the most common local side effect, and headache/fatigue (53.6%), muscle pain (33.2%), malaise (25%), chills (23%), and joint pain (21.2%) were the most common systemic side effects. The vast majority (84.9%) of side effects resolved within 1-3 days post-vaccination; Conclusions: the mRNA-based vaccines were associated with a higher prevalence of local side effects (78.3% vs. 70.4%; Sig. = 0.064), while the viral vector-based vaccine was associated with a higher prevalence of systemic side effects (87.2% vs. 61%; Sig. < 0.001). Females and the younger age group were associated with an increased risk of side effects either after mRNA-based or viral vector-based vaccines. The gender- and age-based differences warrant further rigorous investigation and standardized methodology.
CRIS-Team WoS Importer:2021-09-03